ON THE ISSUE OF IMPLEMENTING LANGUAGE LEARNING STRATEGIES IN THE PRACTICE OF THE HIGHER EDUCATION INSTITUTIONS BY MEANS OF INFORMATION TECHNOLOGIES IN ACCORDANCE WITH THE REQUIREMENTS OF THE BOLOGNA PROCESS - VANIVSKA, Oleksandra (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2018)
Introduction. Modern conditions for the development of European higher education lead to the integration of knowledge of foreign languages and innovative technologies. An important place and role among the factors that provide innovative development of education belongs to ’linguistic strategies’, the implementation and updating of which is now given the highest priority in different countries of the world, since it broadens contacts between people, provides communication, promotes understanding and establishes international contacts. Language strategies today are one of the components of intercultural communication, therefore the ability to apply them in real professional work is relevant and expedient. Purpose of the article is to analyze the main aspects of modern information technologies into the system of language learning strategies in higher education institutions. Results. The introduction of information technologies into the implementation system of language learning strategies has certain specific features that determine the essential aspects of this process development. The key ones among these are internationality, parallelism, accessibility, flexibility, modularity, shareability, cost effectiveness, adaptability, teacher’s proficiency, positive effect on the listener, quality, etc. The article focuses on the need of examining the concept of “information culture”, as the ability to work purposefully with information and to use modern information technologies, modern technical means and methods for receiving, processing, and transferring this information. Consequently, the level of information culture of a person is largely responsible for the feasibility of establishing intensive professional educational contacts in modern educational space. One important component of information culture is teachers’ ability to anticipate the consequences of their own actions, to subordinate their interests to society-accepted standards of behaviour, which are developed by the "collective intelligence". The Bologna process is indicative of three major global trends that actively influence the establishment of intensive professional contacts in Ukraine and abroad, so we can speak of a broader process which creates a global intellectual climate, the international academic mobility, it is part of the knowledge-based economy that is emerging and it is closely connected with changes in the established forms of power and influences in the modern world. Conclusions. On the basis of analysis of the modern state of education, it is established multimedia training programmes allow to teach and practice pronunciation in a higher education institution, to master grammar, and listen to "native speakers" at a high professional level. Mastering computer networks makes it possible to obtain many useful materials from training centers via the Internet. The use of foreign experience to implement language learning strategies by means of information technologies in the practice of higher education institutions will make it possible to intensify training of students according to the Bologna agreements.